Effect of Lactoferin on the Rate of Defect Epithelization and Growth of Pathogenic Microflora in Corneal Erosions in the Experiment - A. V. Kolesnikov; I. V. Kirsanova; N. S. Tumanova; M. M. Averina (Oftalʹmologiâ, 2022)
Corneal lesions account for at least 1/4 of all ocular pathologies. This frequency is due to the fact that the outer eye’ shell is constantly exposed to adverse environmental factors and is quickly involved in the pathological process. The most spread disease is corneal erosion, the main treatment of which is the prevention of infectious complications. The widespread prevalence of corneal erosion and antibiotic resistance, which develops with the use of antibacterial drugs, led to the search for alternative therapies, one of which is lactoferrin.The purpose of our work was to study the effect of lactoferrin solution on the rate of corneal erosion epithelization in the experiment, to assess the effect of lactoferrin solution on the growth of pathogenic microflora against the background of corneal deepithelization in the experiment. An experimental model of corneal erosion was reproduced on 12 male chinchilla rabbits, divided into 2 groups (lactoferrin group and placebo group). Total scarification of the cornea was performed with an eye scalpel after preliminary epibulbar anesthesia with 0.4 % oxybuprocaine solution. Inoculations from the conjunctiva of the rabbits’ eyes to whey broth were carried out on the 0th, 3rd and 7th days of the experiment using sterile glass rods in the clinical diagnostic center of the city of Ryazan. Complete epithelialization of the cornea occurred in group 1 from 3 to 5 days, in group 2 — from 4 to 7 days. The average period of epithelialization in group 1 was 3.75 ± 0.62 days. In the second group — 5.42 ± 0.79 days. The use of a lactoferrin solution at a concentration of 0.5 mg/ml 3 time per day led to an acceleration of corneal epithelialization. In both groups, regardless of therapy, complete epithelialization of the cornea occurred by the 7th day. As a result of the experiment, there was no growth of microflora against the background of corneal de-epithelialization. Our data indicate that the use of a lactoferrin solution led to the suppression of the growth of pathogenic microflora, while placebo did not affect the growth of pathogenic microorganisms.